Gadolinium(III) Complexes with N-Alkyl-N-methylglucamine Surfactants Incorporated into Liposomes as Potential MRI Contrast Agents. (10th August 2015) - Silva, Simone Rodrigues; Duarte, Érica Correia; Ramos, Guilherme Santos; Kock, Flávio Vinícius Crizóstomo; Andrade, Fabiana Diuk; Frézard, Frédéric; Colnago, Luiz Alberto; Demicheli, Cynthia
Abstract : Complexes of gadolinium(III) with N-octanoyl-N-methylglucamine (L8) and N-decanoyl-N-methylglucamine (L10) with 1 : 2 stoichiometry were synthesized and characterized by elemental analysis, electrospray ionization-tandem mass spectrometry (ESI-MS), infrared (IR) spectroscopy, and molar conductivity measurements. The transverse (r 2 ) and longitudinal (r 1 ) relaxivity protons were measured at 20 MHz and compared with those of the commercial contrasts. These complexes were incorporated in liposomes, resulting in the increase of the vesicle zeta potential. Both the free and liposome-incorporated gadolinium complexes showed high relaxation effectiveness, compared to commercial contrast agent gadopentetate dimeglumine (Magnevist). The high relaxivity of these complexes was attributed to the molecular rotation that occurs more slowly, because of the elevated molecular weight and incorporation in liposomes. The results establish that these paramagnetic complexes are highly potent contrast agents, making them excellent candidates for various applications in molecular MR imaging.